Malintzin: The Buried Voice of the Spanish Conquest - Abang, Jasmine A. (The Toro Historical Review, 2020)
The Mexican Conquest is one of the most significant events in world history. However, for centuries, the dominant narrative has been a Eurocentric portrayal that presumes Hernán Cortés and other conquistadors to be heroic, noble, and competent to maneuver through México with little to no opposition. Additionally, it silences Indigenous voices of the 1519 Spanish Conquest and omits the acknowledgment of Indigenous contributions to Spanish success. Matthew Restall’s Seven Myths of the Spanish Conquest pushes against the dominant Eurocentric narrative of the Conquest. In particular, Restall brings an Indigenous woman, Malintzin, the interpreter of Hernán Cortés, to the forefront. With support from translated Nahuatl texts and pictographs and sixteenth-century Spanish sources, Malintzin’s voice becomes visible. Two core Indigenous sources that molded Restall’s arguments are the Florentine Codex, a Mexica source created a generation post-Conquest, and the Lienzo de Tlaxcala, representing an Indigenous ally perspective. Through these sources, Malintzin emerges as a central figure with a multi-skill set of quick language acquisition, the ability to navigate high-risk scenarios, interpreting with cultural mediation and sensitivity, plus the utilization of different linguistic registers. Her skills allowed her to make a conscious decision to become Cortés’ interpreter and proved to be indispensable when it comes to Spanish-Indigenous communication during the Conquest.